RELIGIOUS CONVERSION AND SOCIAL CHANGE THE STORY OF PAN LOTING FROM BALI IN 1931 - Agus Joko Manteus (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2023)
The island of Bali is famous for its unique people and culture in daily life. realized through religion, customs, culture, and the order of society that is inseparable from one another. Several missionary envoys carried out gospel preaching in Bali from the Portuguese era to the Dutch colonial period. Many experienced obstacles both internal and external. Internally, there was a prohibition on the part of the colonizers who did not allow the spread of Christianity on the island of Bali. And external obstacles: in Balinese society that clings to the teachings of Hinduism, the conditions of various rules, attachment to the ancestors of the ancestors, and the customs that are inherent in the order of life of the people. In this study, explained, the cause of a person's conversion to religion, and the main role is a prominent wizard in the Buduk area, whose name is Pan Loting. The purpose of this study was to analyze the background of religious conversion and social changes in society in 1931 in the field of religion. The research method used is the historical research method. The conclusion of this study is the strength of religious conversion experienced through supernatural powers.